2017
DOI: 10.1063/1.4973310
|View full text |Cite
|
Sign up to set email alerts
|

Competition between Al2O3 atomic layer etching and AlF3 atomic layer deposition using sequential exposures of trimethylaluminum and hydrogen fluoride

Abstract: The thermal atomic layer etching (ALE) of AlO can be performed using sequential and self-limiting reactions with trimethylaluminum (TMA) and hydrogen fluoride (HF) as the reactants. The atomic layer deposition (ALD) of AlF can also be accomplished using the same reactants. This paper examined the competition between AlO ALE and AlF ALD using in situ Fourier transform infrared (FTIR) vibrational spectroscopy measurements on AlO ALD-coated SiO nanoparticles. The FTIR spectra could observe an absorbance loss of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
76
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(81 citation statements)
references
References 29 publications
5
76
0
Order By: Relevance
“…9,20 This trend is likely related to a reduced amount of HF adsorbed on the surface at higher temperatures, leading to decreased TMA adsorption in the precursor halfcycle, which is analogous to dehydroxylation for metal oxide ALD. 22 A transition from AlF 3 ALD to Al 2 O 3 atomic layer etching (ALE) at temperatures above 250 C, as found by Lee et al, was however not observed. This difference can be explained by the fact that our actual sample temperature is lower than the set table temperature due to reduced thermal contact in vacuum (see also the supplementary material).…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…9,20 This trend is likely related to a reduced amount of HF adsorbed on the surface at higher temperatures, leading to decreased TMA adsorption in the precursor halfcycle, which is analogous to dehydroxylation for metal oxide ALD. 22 A transition from AlF 3 ALD to Al 2 O 3 atomic layer etching (ALE) at temperatures above 250 C, as found by Lee et al, was however not observed. This difference can be explained by the fact that our actual sample temperature is lower than the set table temperature due to reduced thermal contact in vacuum (see also the supplementary material).…”
mentioning
confidence: 84%
“…20,21 Moreover, Dumont and George found that the temperature dependence of the growth per cycle (GPC) can be explained by the amount of HF adsorbed on AlF 3 , which decreases with temperature. 22 In this work, SF 6 plasma was explored as the co-reactant for ALD of metal fluorides. Using trimethylaluminum [TMA, Al(CH 3 ) 3 ] as precursor and SF 6 plasma as F-source, high-purity AlF 3 films were deposited in an Oxford Instruments FlexAL TM ALD reactor.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The AlF 3 deposition from TMA and HF showed an interesting etching reaction: above 250 • C the precursor pulses etched the AlF 3 film [143,149]. This reaction has later been exploited in developing atomic layer etching processes [170][171][172]. The AlF 3 process has been successfully utilized in protecting freestanding LiCoO 2 /MWCNT (multi-walled carbon nanotube)/nanocellulose fibril electrodes, showing better protection at high potentials compared to the more common artificial SEI material Al 2 O 3 [173].…”
Section: Ald Of Metal Fluorides Using Hf As the Fluorine Sourcementioning
confidence: 99%
“…The most critical problem lies with the construction of the anode. This is because typical anode materials such as AlF 3 , CaF 2 , LaF 3 and MgF 2 have wide band gaps (E g) of ~10.8 eV 16 , ~11.8 eV 17,18 , ~10.5 eV 19 , and ~11.8 eV 20 , respectively.…”
Section: Introductionmentioning
confidence: 99%